PENERAPAN MODEL PEMBELAJARAN ADVANCE ORGANIZERS UNTUK MENINGKATKAN PERHATIAN DAN PRESTASI BELAJAR SISWA (Studi pada Mata Pelajaran Komputer dan Jaringan Dasar Kelas X TKJ di SMK Negeri 1 Jarai) - Ahmad Ansori (UNIB Press, 2021)
This study aims to describe the application of the Advance Organizers learning model to increase student attention and learning achievement in Computer and Basic Network subjects in the tenthgrade students of TKJ at SMK Negeri 1 Jarai. The research design used was classroom action research and quasi-experimental. The research subjects were students of class X.a TKJ SMK Negeri 1 Jarai even semester of the 2020/2021 school year. For the quasi-experimental sample, class X.b and class X.c as the control class. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean, percentage, and t-test. The results showed that the application of the Advance Organizers learning model could increase student attention and learning achievement in Computer and Basic Network subjects of the tenthgrade students of TKJ at SMK Negeri 1 Jarai.